# 6(7x-(7-2y+2x)+5y)=

## Simple and best practice solution for 6(7x-(7-2y+2x)+5y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6(7x-(7-2y+2x)+5y)= equation:

Simplifying
6(7x + -1(7 + -2y + 2x) + 5y) = 0

Reorder the terms:
6(7x + -1(7 + 2x + -2y) + 5y) = 0
6(7x + (7 * -1 + 2x * -1 + -2y * -1) + 5y) = 0
6(7x + (-7 + -2x + 2y) + 5y) = 0

Reorder the terms:
6(-7 + 7x + -2x + 2y + 5y) = 0

Combine like terms: 7x + -2x = 5x
6(-7 + 5x + 2y + 5y) = 0

Combine like terms: 2y + 5y = 7y
6(-7 + 5x + 7y) = 0
(-7 * 6 + 5x * 6 + 7y * 6) = 0
(-42 + 30x + 42y) = 0

Solving
-42 + 30x + 42y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 30x + 42 + 42y = 0 + 42

Reorder the terms:
-42 + 42 + 30x + 42y = 0 + 42

Combine like terms: -42 + 42 = 0
0 + 30x + 42y = 0 + 42
30x + 42y = 0 + 42

Combine like terms: 0 + 42 = 42
30x + 42y = 42

Add '-42y' to each side of the equation.
30x + 42y + -42y = 42 + -42y

Combine like terms: 42y + -42y = 0
30x + 0 = 42 + -42y
30x = 42 + -42y

Divide each side by '30'.
x = 1.4 + -1.4y

Simplifying
x = 1.4 + -1.4y`